The European Union as a '3-D' Constitutional Space. Issue 2 (June 2014) - Simoncini, Andrea
This article advances the hypothesis that the European constitution has to be considered a 'space': that in addition to the 'classical' judicial and political dimensions, there is a third constitutional dimension – the civic. A distinctive feature of European political thought and constitutional practice is that public authority has always been coupled with an autonomous 'civil sphere' and that social formations and their rights, as individuals, pre-existed the nation-state. The totalitarian 'trauma' between the two world wars, and the decisive role political parties played in it, produced the idea, rooted in the very origin of the European Treaties, that representative democracy must be complemented by social or corporative representation/participation. This article analyses European primary law, finding two subsequent 'constitutionalization waves'. This leads to the conclusion that there is in fact a 'corpus juris' (concerning the 'social dialogue', the European Economic and Social Committee (EESC), the Commission's consultations, the European Citizen's Initiative (ECI), lobbying) expressing this third civic dimension of the European constitution. This conclusion does not claim that each of the three dimensions is currently equally equipped and effective: it ranges from a highly developed legal/judicial dimension, to a weaker-but-growing institutional/political dimension, and eventually to an embryonic-almost-non-existent social/civic dimension.